2022
DOI: 10.1177/15394492221104075
|View full text |Cite
|
Sign up to set email alerts
|

The Weekly Calendar Planning Activity to Assess Functional Cognition in Parkinson Disease

Abstract: The Weekly Calendar Planning Activity (WCPA) may improve understanding of functional cognition in people with Parkinson disease (PwPD) without dementia. We aimed to determine if WCPA performance (a) discriminates between PwPD with and without cognitive impairment and healthy controls and (b) correlates with other indicators of cognition and daily function. This was a cross-sectional study. Parkinson disease (PD) participants without dementia were divided into normal cognition (PD-NC, n = 25) and possible mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…This is in line with prior studies on the WCPA with other neurological conditions like multiple sclerosis (Goverover et al, 2020), and adolescents with ABI (Doherty et al, 2022), which have also found a significant relationship between accurate performance and strategy use in WCPA and established measures of EF. Furthermore, the relationship between the total accuracy score and neuropsychological tests that measure EF has also been observed in studies with Parkinson's patients (Foster et al, 2022). These findings support prior work highlighting the role of EF for successful everyday activity completion (Poncet et al, 2017;Lipskaya-Velikovsky et al, 2018).…”
Section: Relationship and Predictive Value Of The Spanish Wcpa-measur...supporting
confidence: 80%
“…This is in line with prior studies on the WCPA with other neurological conditions like multiple sclerosis (Goverover et al, 2020), and adolescents with ABI (Doherty et al, 2022), which have also found a significant relationship between accurate performance and strategy use in WCPA and established measures of EF. Furthermore, the relationship between the total accuracy score and neuropsychological tests that measure EF has also been observed in studies with Parkinson's patients (Foster et al, 2022). These findings support prior work highlighting the role of EF for successful everyday activity completion (Poncet et al, 2017;Lipskaya-Velikovsky et al, 2018).…”
Section: Relationship and Predictive Value Of The Spanish Wcpa-measur...supporting
confidence: 80%
“…Assessments of neurocognitive skills support the understanding of performance, but is not a substitute for performance-based testing of functional cognition. When neurocognitive measures and functional cognitive measures are administered together, correlations rarely exceed the moderate range suggesting that they are indeed measuring disparate constructs (Boone & Wolf, 2021; Foster et al, 2022). We are not arguing against the importance of neurocognitive assessment.…”
Section: Relationship Of Neurocognitive Assessment To Performance-bas...mentioning
confidence: 99%
“…We recommend that functional cognitive and neurocognitive measures be used in tandem to create a comprehensive understanding of cognitive function. There is ample evidence supporting a multi-level approach that combines neurocognitive data with functional data to improve identification of individuals with both cognitive impairment and functional cognitive deficits (Dham et al, 2020; Foster et al, 2022; Gonzalez et al, 2021). However, the use of brief global screening measures (e.g., Mini Mental State Exam, the Montreal Cognitive Assessment [MOCA], and the Neurobehavioral Cognitive Status Examination; Folstein et al, 1975; Kiernan et al, 1987; Nasreddine et al, 2005) to infer real-world IADL performance capacity is beyond the scope of the original purpose of the measures (Burgess et al, 2006).…”
Section: Relationship Of Neurocognitive Assessment To Performance-bas...mentioning
confidence: 99%
See 1 more Smart Citation
“…The WCPA is a multistep activity of scheduling a list of appointments into a weekly schedule that requires working memory, planning, shifting, inhibition, and self-monitoring [23]. The 17-item version of the WCPA differentiated between healthy controls (HCs) and individuals (known-group validity) with multiple sclerosis (MS) [24] and PD with a mean duration of 6.7 years from diagnosis [25]. The WCPA's convergent and ecological validity has also been established specifically for MS [24].…”
Section: Introductionmentioning
confidence: 99%